Genotypic Variation in Epicuticular Wax of Rice - O'Toole, J.C.; Cruz, R.T. (Wiley, 1983)
Improvement of rice (Oryza sativa L.) cultivars for drought‐prone regions involves assessment of genotypic variation within specific adaptive mechanisms. This note describes the variation in amount of epicuticular wax (EW) among 30 rice cultivars from varying hydrological origins. Leaf wax extracts were analyzed by gas liquid chromatography (GLC) for quantitative and qualitative differences. A five‐fold difference in total EW per unit leaf area was found among cultivars. Total amount of EW and the amount in GLC peak 3 were positively correlated with cultivars originating at higher elevations. Results suggest the relative amount of an unknown wax constituent (GLC peak 3) is associated with adaptation of rice cultivars to hydrologically drier habitats.